DEPOSIT PORTFOLIO ANALYSIS METHODOLOGY - Shermukhamedov Bekhzodjon Usmonovich (American Journals, 2023)
This article is devoted to the role and analysis of commercial banks in the economy of our republic, studied the data of their resource base, deposit operations carried out by commercial banks, analyzed the data of the deposit base. The importance of deposits in the activities of commercial banks is substantiated and the results of studies aimed at increasing the deposit base of banks operating in Uzbekistan are presented.
Keywords: Deposit, deposit base, deposit policy, transformation, diversification, balance sheet, bank balance sheet, deposit operations, time deposits.